Intergenerational Mobility between and within Canada and the United States - Marie Connolly; Miles Corak; Catherine Haeck (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2019)
Intergenerational income mobility is lower in the United States than in Canada, but varies significantly within each country. Our sub-national analysis finds that the national border only partially distinguishes the close to one thousand regions we analyze within these two countries. The Canada-US border divides Central and Eastern Canada from the Great Lakes regions and the Northeast of the United States. At the same time some Canadian regions have more in common with the low mobility southern parts of the United States than with the rest of Canada, and the fact that these areas represent a much larger fraction of the American population also explains why mobility is lower in the United States.
Keywords: D63; J61; J62; 330; intergenerational mobility; equality of opportunity; geography